Economic Complexity, Institutions, and Property Rights - Aribah Aslam; Maryam Ishaq; Ghulam Ghouse; Bismillah Khan (European Management Studies)
Objectives/Background: Property rights play a fundamental role in economics through rights to asset and resource owners, thereby enhancing their economic efficiency. The study investigates the relationship between property rights and economic complexity across countries classified by income levels, including high, middle, and low-income nations. Methods: The study utilized Robust Least Square (RLS) to obtain results from a secondary data set. Results: Our analysis reveals a positive relation between economic complexity and property rights across all income groups. It is suggested to have potential developmental paths for countries based on their income status such as those of low income and middle income groups. More specifically, it is proposes that low-income countries could benefit from the institutional improvements observed in high middle-income countries group. Whereas, high middle-income countries may find help in modeling their institutions after those of high-income countries. The approaches may help sustain and enhance institutions and foster an environment conducive to economic complexity. Conclusion: This research contributes valuable insights into the interplay between economic complexity and property rights across diverse income contexts, offering potential strategies for policymakers to enhance property rights and drive inclusive economic development.